A predictive tool to evaluate disc brake squeal propensity. Part 1: The model philosophy and the contact problem. (20th February 2004) - Lee, Y.S.; Brooks, P.C.; Barton, D.C.; Crolla, D.A.
This paper is the first in a series of three that describe an integrated approach to the analysis of disc brake squeal. The technique is based around the use of a parametric finite element representation of the disc-pad assembly. In this paper, the problem is introduced together with the philosophy that underpins the model. The procedure adopted to solve the non-linear contact problem, which occurs at the friction pair interface, is illustrated and typical results presented that show how the contact behaviour is influenced by change in interface friction levels, hydraulic actuation pressure and loading mechanism.